2009
DOI: 10.1352/1934-9556-47.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction and Sense of Well Being Among Medicaid ICF/MR and HCBS Recipients in Six States

Abstract: Self-reported satisfaction and sense of well-being were assessed in a sample of 1,885 adults with intellectual and developmental disabilities receiving Medicaid Home and Community Based Services (HCBS) and Intermediate Care Facility (ICF/MR) services in 6 states. Questions dealt with such topics as loneliness, feeling afraid at home and in one's neighborhood, feeling happy, feeling that staff are nice and polite, and liking one's home and work/day program. Loneliness was the most widespread problem, and there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 10 publications
2
35
1
Order By: Relevance
“…Like the previous study, this difference existed at each level of intellectual disability. We bave sbown elsewbere tbat people wbo cbose wbere and witb wbom tbey live experienced a range of more positive lifestyle outcomes (Stancliffe, Lakin, Taub, Chiri, & Byun, 2009). In addition to having little support-related choice, the absence of key cboices about wbere and witb wbom to live may bave consequences sucb as increased loneliness, decreased liking of one's bome, and decreased reported bappiness.…”
Section: Areas For Further Studymentioning
confidence: 99%
“…Like the previous study, this difference existed at each level of intellectual disability. We bave sbown elsewbere tbat people wbo cbose wbere and witb wbom tbey live experienced a range of more positive lifestyle outcomes (Stancliffe, Lakin, Taub, Chiri, & Byun, 2009). In addition to having little support-related choice, the absence of key cboices about wbere and witb wbom to live may bave consequences sucb as increased loneliness, decreased liking of one's bome, and decreased reported bappiness.…”
Section: Areas For Further Studymentioning
confidence: 99%
“…Concerns included ‘the possible lack of support’ from staff, potential boredom because of living alone and issues of safety. Stancliffe et al . (2009) compared self‐reported levels of satisfaction and sense of well‐being in a sample of 1885 across community‐based services and intermediate care facilities in six US states reporting consistent benefits of small settings with choice of where and with whom to live and for individuals living with families.…”
Section: Introductionmentioning
confidence: 99%
“…Gardner & Carran (2005) found an association between the personal outcome ‘People chose where and with whom to live’ and several other important individual outcomes such as ‘People are safe’ and ‘People are free from abuse and neglect’. Stancliffe et al . (2009) reported that individuals with greater choice of living companions and of where to live had better outcomes in four of six areas examined: loneliness (only for choice of whom to live with), feeling happy, home staff are nice, and liking home (the other two areas showed no significant differences).…”
Section: Introductionmentioning
confidence: 99%
“…For example, choosing between several group homes may provide genuine choice about where to live, but no meaningful choice of housemates. Stancliffe et al . (2009) reported only a modest correlation between choice of living companions and choice of where to live ( r s = 0.42, P < 0.001).…”
Section: Introductionmentioning
confidence: 99%